Abnormal cerebellar network and effective connectivity in sudden and long-term sensorineural hearing loss - Hua, Jin-Chao; Xu, Xiao-Min; Xu, Zhen-Gui; Xue, Yuan; Xu, Jin-Jing; Hu, Jing-Hua; Wu, Yuanqing; Chen, Yu-Chen (Frontiers in Aging Neuroscience, 2022)
Sudden sensorineural hearing loss (SSNHL) is a common otology emergency and some SSNHL will develop into long-term hearing loss (LSNHL). However, whether SSNHL and LSNHL has similar psychiatric patterns remains unknown, as well as the neural substrates. Increasing evidence has proved that the cerebellar network plays a vital role in hearing, cognition processing and emotion control. Thus, we recruited 20 right SSNHL (RSSNHL), 20 right LSNHL (RLSNHL) and 24 well-matched healthy controls to explore the cerebellar patterns among three groups. Every participant underwent pure tone audiometry tests, neuropsychological evaluations and MRI scanning. Independent component analysis (ICA) was carried out on the MRI data and the cerebellar network was extracted. Granger causality analysis (GCA) were conducted using the significant cerebellar region as a seed. Person’s correlation analysis was computed between imaging characteristics and clinical features. ICA found the effect of group on right cerebellum lobule V for cerebellar network. Then, we found decreased outflow from right cerebellum lobule V to right middle orbitofrontal cortex, inferior frontal gyrus, anterior cingulate cortex, superior temporal gyrus and dorsal lateral prefrontal cortex in RSSNHL group in GCA analysis. No significance was found in RLSNHL subjects. Additionally, the RSSNHL group showed increased effective connectivity from right middle frontal gyrus (MFG) and the RLSNHL group showed increased effective connectivity from right insula and temporal pole to right cerebellum lobule V. Moreover, connections between right cerebellum lobule V and mean time series of cerebellar network in was negatively correlated with anxiety score in RSSNHL and negatively correlated with depression scores in RLSNHL too. Effective connectivity from right MFG to right cerebellum lobule V could predict anxiety status in RSSNHL subjects. Our results may prove potential imaging biomarkers and treatment targets for hearing loss in future work.